Reforming Educational Governance and Management in Egypt: National and International Actors and Dynamics - Ginsburg, Mark; Megahed, Nagwa; Elmeski, Mohammed; Tanaka, Nobuyuki (Education Policy Analysis Archives, 2010)
This historical case study examines the rhetoric, action, and outcomes of educational policy reforms in Egypt during the first quarter-century of the presidency of Mohamed Hosni Mubarak. The findings are based on an extensive review of Egyptian government, international organization, and project documents as well as interviews with key stakeholders. The study focused on proposed and implemented changes in the organization and distribution of various governance and management functions across school/community, district/idarra, governorate/muddiriya, and national/central levels of the education system. During the period under review Egypt experienced movement though uneven toward increased decentralization, with calls for deconcentration of responsibility in 1981, Ministry of Education actions that restricted local decision-making authority in the 1990s, and some concerted efforts toward delegation and devolution of authority as well as responsibility after 2001. In terms of community participation, during this period there were calls for and actions toward implementing broader and deeper forms and degrees of involvement by parents, civil society, and businesses. We draw on the following concepts to analyze a develop an account of these developments: institutional framework, financial resources, system leaders' capacity and political will, civil society's leaders' capacity and political will, global dynamics, and the role of international organizations